2022
DOI: 10.1021/acs.molpharmaceut.2c00745
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preclinical Evaluation of a 68Ga-Labeled Pyridine-Based Benzamide Dimer for Malignant Melanoma Imaging

Abstract: Benzamide (BZA), a small molecule that can freely cross cell membranes and bind to melanin, has served as an effective targeting group for melanoma theranostics. In this study, a novel pyridine-based BZA dimer (denoted as H-2) was labeled with 68 Ga ([ 68 Ga]Ga-H-2) for positron emission tomography (PET) imaging of malignant melanomas. [ 68 Ga]Ga-H-2 was obtained with high radiochemical yield (98.0 ± 2.0%) and satisfactory radiochemical purity (>95.0%). The specificity and affinity of [ 68 Ga]Ga-H-2 were confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In some cases, dimerization or multimerization proves to be an effective strategy for enhancing the tumor uptake and retention of radiopharmaceuticals compared with monomers. , Representative examples benefiting from the homodimeric approach include radiolabeled RGD/FAPI/PSMA/folic acid/benzamide dimers, which target integrin α v β 3 , FAP, PSMA, folate receptor, and melanin, respectively. Furthermore, previous studies have demonstrated that polyethylene glycol linkers (PEGylation) acted as hydrophilic modification to modulate the pharmacokinetics of dimeric small molecule–radio conjugates. ,,,, In the present study (Figure ), on the basis of the OncoFAP (an ultrahigh-affinity small organic motif for FAP reported by Millul et al), a bivalent FAPI precursor (HYNIC-BiOncoFAP, denoted as HF 2 ) coupled with mini-PEG spacers and the hydrazinonicotinamide (HYNIC) group was designed and synthesized with the goal of improving tumor uptake and image contrast. As illustrated in Figure A, with the introduction of coligands such as tricine, trisodium triphenylphosphine-3,3′,3″-trisulfonate (TPPTS), ethylenediamine- N,N′ -diacetic acid (EDDA), and sodium triphenylphosphine-3-monosulfonate (TPPMS), HF 2 was radiolabeled with 99m Tc through one-pot synthesis to form [ 99m Tc]­Tc-TPPTS-HF 2 , [ 99m Tc]­Tc-EDDA-HF 2 , and [ 99m Tc]­Tc-TPPMS-HF 2 complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, dimerization or multimerization proves to be an effective strategy for enhancing the tumor uptake and retention of radiopharmaceuticals compared with monomers. , Representative examples benefiting from the homodimeric approach include radiolabeled RGD/FAPI/PSMA/folic acid/benzamide dimers, which target integrin α v β 3 , FAP, PSMA, folate receptor, and melanin, respectively. Furthermore, previous studies have demonstrated that polyethylene glycol linkers (PEGylation) acted as hydrophilic modification to modulate the pharmacokinetics of dimeric small molecule–radio conjugates. ,,,, In the present study (Figure ), on the basis of the OncoFAP (an ultrahigh-affinity small organic motif for FAP reported by Millul et al), a bivalent FAPI precursor (HYNIC-BiOncoFAP, denoted as HF 2 ) coupled with mini-PEG spacers and the hydrazinonicotinamide (HYNIC) group was designed and synthesized with the goal of improving tumor uptake and image contrast. As illustrated in Figure A, with the introduction of coligands such as tricine, trisodium triphenylphosphine-3,3′,3″-trisulfonate (TPPTS), ethylenediamine- N,N′ -diacetic acid (EDDA), and sodium triphenylphosphine-3-monosulfonate (TPPMS), HF 2 was radiolabeled with 99m Tc through one-pot synthesis to form [ 99m Tc]­Tc-TPPTS-HF 2 , [ 99m Tc]­Tc-EDDA-HF 2 , and [ 99m Tc]­Tc-TPPMS-HF 2 complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent among them is malignant melanoma, diagnosed each year in about 1.7% of primary malignancies and contributing to 0.7% of cancer-related deaths. 1 Melanocyte-derived melanoma, usually found in the innermost part of the epidermis (basal layer), is the most malignant type of skin cancer due to its rapid growth rate and numerous metastases. It can spread to various body parts, from draining lymph nodes to distant visceral organs, especially the brain, lungs, bones, and liver.…”
Section: Introductionmentioning
confidence: 99%